2020
DOI: 10.1002/er.5652
|View full text |Cite
|
Sign up to set email alerts
|

Review and clustering of optimal energy management problem studies for industrial microgrids

Abstract: The optimal energy management problem of microgrids is an agenda item for the energy field. Especially industrial microgrids, whose energy demand is high and uninterruptible, need to be managed by a holistic view of optimization. Technical researches in this field are to be enriched with the literature review that looks through various angles. In the scope of this paper, the research literature is reviewed deeply and analyzed with the aim of presenting the gaps. Articles written in English, in the period of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 124 publications
(165 reference statements)
0
6
0
Order By: Relevance
“…It contains important information such as distributed power sources and load types, the configuration of ESS, grid connection, and island forms, and reveals the internal connections of the basic components of MGs. A reasonable MG structure can improve the flexibility and stability of the distribution network, and solve the intermittent problem of renewable energy and the optimal configuration of the ESS 8‐10 …”
Section: Mg Analysis and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains important information such as distributed power sources and load types, the configuration of ESS, grid connection, and island forms, and reveals the internal connections of the basic components of MGs. A reasonable MG structure can improve the flexibility and stability of the distribution network, and solve the intermittent problem of renewable energy and the optimal configuration of the ESS 8‐10 …”
Section: Mg Analysis and Researchmentioning
confidence: 99%
“…A reasonable MG structure can improve the flexibility and stability of the distribution network, and solve the intermittent problem of renewable energy and the optimal configuration of the ESS. [8][9][10] 2.1 | The MG structure analysis MG is a small power generation-transformation-power storage-power transmission-power consumption system. It is usually composed of distributed power sources, energy storage devices, power electronic conversion devices, loads, and other components.…”
Section: Mg Analysis and Researchmentioning
confidence: 99%
“…Outcomes [108]This article provides an overview of the distributed energy supply activity and various systems applied in the energy management system, such as demand response, demand‐side management, and power quality management. This article suggested that several cutting‐edge optimization recommendations would successfully be applied to smart homes, industry, and EV to improve the load curve.[107]The proposed article suggested a systematic controlling methodology based on EMS is analyze on an MG system.[109]The suggested article analyzes the actual problem thoroughly on the optimal energy management approach on the MG. Several objectives, different ESS and power sources are analyzes to how to improve the overall system efficiency.[110]This article discusses several EMS approaches that have been implemented using various technical methods for MG demand‐side management.[111]A valuable result for a deeper understanding of existing research‐specific problems, prospects, possible obstacles, and unanswered questions about future centralized and decentralized EMS innovations are thoroughly described in this article.[112]A large‐scale literature study on HRES outlines a system with broad goals for optimization methods to enable the MG system's efficiency. A study of modeling and implementations of renewable energy production, storage sources, and integration of RESs through future upcoming EMS problems is discussed in detail.[113]This article's primary focus is to summarize the control goals and development of the new methodologies in the MGSC and EMS, which was recently proposed.…”
Section: Current Literature Study On Emsmentioning
confidence: 99%
“…Results indicated how the demand of this factory was moved to improve the total demand peak of the grid, although a comprehensive model of this industry's processes was not presented. In [15], an optimal energy management strategy was presented for the economic operation of industrial microgrids using renewable energy with high impact under both grid operation and grid-connectedto-grid operation modes. This approach was based on group particle swarm optimization, which was considered on a daily planning horizon with a one-time step the renewable energies generation and electric load demand.…”
Section: Introductionmentioning
confidence: 99%